Gathering blossoms under fire - Walker, Alice,Boyd, Valerie (Simon & Schuster, 2022)
For the first time, the edited journals of Alice Walker are gathered together to reflect the complex, passionate, talented, and acclaimed Pulitzer Prize winner of The Color Purple. She intimately explores her thoughts and feelings as a woman, a writer, an African-American, a wife, a daughter, a mother, a lover, a sister, a friend, a citizen of the world. In an unvarnished and singular voice, she explores an astonishing array of events: marching in Mississippi with other foot soldiers of the Civil Rights Movement, led by Martin Luther King, Jr.; her marriage to a Jewish lawyer, defying laws that barred interracial marriage in the 1960s South; an early miscarriage; writing her first novel; the trials and triumphs of the Women's Movement; erotic encounters and enduring relationships; the ancestral visits that led her to write The Color Purple; winning the Pulitzer Prize; being admired and maligned, sometimes in equal measure, for her work and her activism; and burying her mother. A powerful blend of Walker's personal life with political events, this revealing collection offers rare insight into a literary legend
9781476773155
Keywords: Tagebuch; Walker; Alice; Authors; American; African American women authors; Social reformers; Diaries